Towards a unifying domain model of construction safety, health and well-being: SafeConDM. (January 2022) - Li, Beidi; Schultz, Carl; Teizer, Jochen; Golovina, Olga; Melzner, Jürgen
Graphical abstract: Highlights: The AEC industry lacks the standardization of safety concepts and software tools. SafeConDM presents a novel link between safety management and information models. Formalises safety construction rules and mitigation strategies via spatial artefacts. SafeConAI enables hazard analysis and safe construction planning decision support. Real-world use cases provide strong reasons for meaningful practical applications. Abstract: Specific occupational construction safety, health, and well-being related knowledge and information are scattered and fragmented. Despite technological advancements of information and knowledge management, a link between safety management and information models is still missing. In this paper we present first steps towards a unifying formal (logic-based) domain model of construction safety, called SafeConDM, that consists of: (1) a semantically rich ontology of hazard, safety concepts, and concept relationships that builds on, and integrates with, existing construction safety ontologies and building information models; (2) a set of first-order if-then rules linking construction site states with the potential for specific hazards to occur that we define in a novel way using spatial artefacts . We present a prototype software tool, based on our ASP4BIM tool that implements SafeConDM for construction hazard analysis and safe construction planning decision support, and empirically evaluate our tool on three real-world construction building models.